Resistance monitoring and mechanism in the fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) for chlorantraniliprole from Sichuan Province, China - Chen, Hui-Lin; Hasnain, Ali; Cheng, Qing-Hua; Xia, Li-Juan; Cai, Yu-Hao; Hu, Rong; Gong, Chang-Wei; Liu, Xue-Mei; Pu, Jian; Zhang, Lei; Wang, Xue-Gui (Frontiers in Physiology, 2023)
The fall armyworm, Spodoptera frugiperda (Noctuidae: Lepidoptera), is a wide-reaching notorious insect pest of important cereal crops, which has developed resistance to multiple classes of insecticides. It invaded the Sichuan Province of China in 2019. In this study, we performed resistance monitoring of insecticides for 11 field-collected populations from Sichuan, and all the populations were susceptible to emamectin benzoate and chlorpyrifos. The variations in resistance level to indoxacarb (resistance ratio (RR), 9.23–45.53-fold), spinetoram (RR, 4.32–18.05-fold), and chlorantraniliprole (RR, 2.02–10.39-fold) were observed among these populations. To investigate the resistance mechanism of chlorantraniliprole, synergism tests were performed and showed that piperonyl butoxide had a slight synergistic effect on chlorantraniliprole for the QJ-20 population (1.43-fold) in moderate resistance (RR, 10.39-fold) compared with the treatment group without synergist. Furthermore, the expression scanning for resistance-related genes showed that five P450 genes (CYP6AE43, CYP321A8, CYP305A1, CYP49A1, and CYP306A1) and the ryanodine receptor gene (Ryr, chlorantraniliprole target) were overexpressed in the QJ-20 population. These results indicated that the fall armyworm in Sichuan has exhibited diverse susceptibilities to several classes of insecticides, and the overexpression of Ryr and several P450 genes may contribute to the development of resistance in S. frugiperda to chlorantraniliprole.